2004
DOI: 10.1152/ajpgi.00102.2004
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in L-type Ca2+channel expression in feline lower esophageal sphincter

Abstract: In humans and cats, muscle from the lower esophageal sphincter (LES) circular region exhibits greater spontaneous tone than LES sling muscle, whereas the sling muscle is much more responsive to cholinergic stimulation. Despite physiological and pharmacological evidence for the presence of L-type Ca2+ channel current (ICa,L) activity in LES circular muscle, the identity of this channel has not been demonstrated biochemically or electrophysiologically fingerprinted. Furthermore, there is no information on the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
3
15
0
Order By: Relevance
“…Ca 2ϩ currents with similar properties and pharmacology to those in the present study have been reported in feline LES smooth muscle (21). However, other sources of Ca 2ϩ entry exist in esophageal muscle, including nonselective cation channels of the transient receptor potential C (TRPC) family (39).…”
Section: Discussionsupporting
confidence: 78%
“…Ca 2ϩ currents with similar properties and pharmacology to those in the present study have been reported in feline LES smooth muscle (21). However, other sources of Ca 2ϩ entry exist in esophageal muscle, including nonselective cation channels of the transient receptor potential C (TRPC) family (39).…”
Section: Discussionsupporting
confidence: 78%
“…In achalasia, absence of the dominant nitrergic inhibition in the high tone circular muscle (14,25) results in LES pressures equalizing around the sphincter circumference to the higher level of the sling where cholinergic excitation is dominant (45). Reducing LES pressure in vivo with the administration of nifedipine would in large part be directed to the circular portion, because calcium entry in that muscle is largely through L-type calcium channels, whereas that of the sling is largely through non-L-type channels (28). Reduction of LES tone by blockade of ACh release with botulinum toxin would presumably involve primarily the cholinergic innervation of the sling muscle (35) and suggests that the injection should be directed mainly to the left.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of LES tone by blockade of ACh release with botulinum toxin would presumably involve primarily the cholinergic innervation of the sling muscle (35) and suggests that the injection should be directed mainly to the left. The regional differences between sling and circular muscles also provide different options for the surgical management of achalasia (17,23,28,45,51). Cutting the circular muscle may be all that is necessary to relieve the functional obstruction while leaving the cholinergic sling activity will protect against reflux.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The macroscopic arrangement of LOS circular smooth fibres of the inner muscle in humans and pigs is similar, with short transverse muscle clasps on the lesser curve side (clasp fibres) and long oblique gastric sling fibres in the angle of His of the greater curvature on the left side 4,5 . Differences in function between clasp and sling fibres have been attributed to regional specialization relating to smooth muscle cell physiology 1,6,7 , distribution and function of enteric motor neurones (EMNs) 8 -10 , and extrinsic vagal input 11 .…”
Section: Introductionmentioning
confidence: 99%